Feeling Guilt and Shame Upon Psychological Dating Violence Victimization in College Women: The Further Role of Sexism - Oflaz, Çiğdem (Journal of interpersonal violence, 2023)
Dating violence is manifested in different forms between romantic partners. Psychological violence, the most common form of dating violence, is more likely to affect women, eliciting feelings such as shame and guilt. The robust relationship of sexism to psychological dating violence victimization (PDVV) is well-documented but whether PDVV serves as a mechanism linking sexism to guilt and shame remains unexplored. This study, therefore, investigated the potential mediating role of PDVV in the association between sexist attitudes and feelings of guilt and shame. Dating college women (N = 219) from Turkey, an honor culture in which one’s self-worth lies on one’s evaluation as well as the assessment of what others think, participated in the study. High rates of PDVV were found in this culture, and structural equation modeling revealed that PDVV mediated the relationship between sexism and feelings of guilt and shame. These findings are discussed in terms of their implications for future research and how sexist attitudes might be challenged to reduce the adverse emotional effects experienced by women who are victims of psychological dating violence.